Βαθμονόμηση κυκλοφοριακών μοντέλων προσομοίωσης με τη χρήση του αλγορίθμου SPSA - Μάρκου, Ιουλία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2014)
Traﬃc simulation models, with the default parameter values, are not suitable for all studies. The characteristics of the network, the drivers behavior etc. are constantly changing. Each model represents this diversity through its parameters. When the basic format of the model is known, and there is enough data available, calibration is the procedure that aims at estimating the parameters that will lead to results, as close as possible to the observed ones in the ﬁeld. The calibration is a crucial step for the successful application of traﬃc simulation models in transportation planning and real traﬃc management. In this thesis, the calibration methodology using the algorithm Simultaneous Perturbation Stochastic Approximation (SPSA) is studied. The behavior of the algorithm is analyzed through various applications. Several particular behaviors are identiﬁed for which solutions are suggested. The algorithm was prepared to apply even in a quite demanding calibration workload, that of the expressway network of Singapore using the DymaMIT. Results indicate that SPSA successfully manages to reach the optimal solution, however with diﬀerent speed and eﬃciency each time. The parameter values were proved to be very important, especially the parameters a, alpha and c. Mismatches could even lead to the ﬁnal failure of the algorithm’s convergence to the optimal solution.